Horizontal and vertical transmission of microsporidia Nosema pyrausta and Nosema bombycis in the predatory bug Podisus maculiventris (Hemiptera: Pentatomidae) - Arina S. Rumiantseva; Anastasia N. Ignatieva; Inna V. Grushevaya; Alsu M. Utkuzova; Nina V. Binitskaya; Anastasia G. Kononchuk; Ekaterina G. Kozlova; Anastasia A. Khodzhash; Yuri S. Tokarev (Acta Biologica Sibirica)
Predatory insects play an important role in the regulation of arthropod’s numbers. When they counteract with the diseased prey, the entomopathogenic microorganisms may be disseminated mechanically or parasitize such secondary hosts. Microsporidia are wide-spread pathogens of insects with diverse host ranges, and infection of entomophagous hosts is not uncommon. In the present study, the spined soldier bug nymphs were fed with the adzuki bean borer larvae infected with Nosema pyrausta (A. Paillot) J. Weiser, 1961 or the silkworm larvae infected with N. bombycis Nägeli, 1857. Both pathogens were infective to the predator at the prevalence level of 15-30%. The former pathogen displayed a decrease of prevalence level in the filial generation to as low as 5 % and no infection in consequent generations. The latter could only be transmitted to bugs horizontally and no infections in the filial generation was found. This indicates low (or no) risk of vertical transmission of these two pathogens, making them suitable for combined application with the predatory bug in the integrated pest management programmes.